2016
DOI: 10.1007/s00167-016-4096-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting cartilage repair after medial opening-wedge high tibial osteotomy

Abstract: Level IV, therapeutic case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 29 publications
6
45
1
2
Order By: Relevance
“…[13], we could not find any effect of BMI on cartilage regeneration, contrary to Kumagai et al [11] and Kim et al [12]. The relatively low BMI of our study sample might have been the reason why there was no association with cartilage regeneration.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…[13], we could not find any effect of BMI on cartilage regeneration, contrary to Kumagai et al [11] and Kim et al [12]. The relatively low BMI of our study sample might have been the reason why there was no association with cartilage regeneration.…”
Section: Discussioncontrasting
confidence: 89%
“…Moreover, when the kissing lesions is present, it can possibly affect cartilage regeneration by disturbing the stable position of marrow stem cells during the regeneration process. Like in our study, most investigations assessing cartilage regeneration have shown that a larger cartilage defect is associated with poor cartilage regeneration [11,13,24].…”
Section: Discussionsupporting
confidence: 76%
“…Kumagai et al [15] reported Body Mass Index(BMI), initial cartilage and postoperative limb alignment were major factors on HTO. Age, gender and clinical results were not affect the cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that a regenerative response of articular cartilage was observed in several cases after HTO [5][6][7][8][9][10][11][12]. These reports involved either OWHTO or CWHTO, and to the best of our knowledge, no study has directly compared postoperative cartilage repair between OWHTO and CWHTO.…”
Section: Introductionmentioning
confidence: 93%